The importance of scientific-technological research in metallurgy - León Delgado, Elard Felipe (1998)
The problems about underdevelopment are a matter of concern alike from politicians, economists, through the military, doctors, psychologists, to administrators, philosophers, essayists, and many more professionals such as engineers. In order to try to give a solution, various solutions are proposed, but whatever the chosen path, access to a modern society, the final objective of development, involves achieving active participation from Engineering, and in particular from metallurgical engineering.